The Influence of School Culture and Organizational Commitment on Teacher’s Performance in Senior High Schools in Tanjung Lubuk Sub-District - Hidayatullah, Sanul; Fitria, Happy; Wahidy, Achmad (Yayasan Sembilan Pemuda Indonesia, 2023)
The purpose of this study was to determine the effect of school culture and organizational commitment on teacher performance in high schools in Tanjung Lubuk district. The sample size taken was 70 teachers in high schools in Tanjung Lubuk District. The sampling technique was purposive sampling, where the respondents taken were some of the teachers in SD Negeri Gugus 1 Lubuk Besar District, Central Bangka Regency, Tanjung Lubuk. Data collection was carried out by distributing questionnaires using a 5-point Likert scale to measure 67 statement items. The analysis technique used is multiple linear regression analysis. The results showed that there was an influence of school culture and organizational commitment on teacher performance Second, there is an influence of school culture on teacher performance Third, there is an influence of organizational commitment on teacher performance.